Unveiling the interfacial charge extraction kinetics in inorganic perovskite solar cells with formamidinium lead halide (FAPbX3) nanocrystals. (1st January 2020) - Duan, Jialong; Wei, Jiahu; Tang, Qunwei; Li, Qinghua
Graphical abstract: Highlights: Formamidinium lead halide perovskite quantum dots have been fabricated. The charge extraction and transfer at perovskite/carbon interface is accelerated. The device yields an enhanced efficiency of 8.55% under one standard solar irradiation. The performances are nearly unchanged after storage for 60 days in air atmosphere. Abstract: Rapid charge extraction and transfer is a crucial prerequisite to achieve high-performance perovskite solar cells, however, the notorious non-radiative recombination pathways limit the further efficiency enhancement owing to the energy barriers between charge transporting layers and perovskite layers. Aiming to realize the accelerated charge extraction and reduced charge loss, in the current work, formamidinium lead halide (FAPbX3, X = Cl, Br, or I) perovskite nanocrystals are successfully fabricated using high-melting-point ligands to modify the perovskite/carbon interface in all-inorganic CsPbBr3 perovskite solar cells, which are regarded as promising photovoltaic device because of their superior stability under rigorous conditions comparing to organic-inorganic hybrid perovskite solar cells. By optimizing the composition of FAPbX3 perovskite nanocrystals, an elevated power conversion efficiency up to 8.55% is achieved owing to the enhanced charge transfer kinetics and reduced charge recombination loss, demonstrating the importance of interface control in high-performance photovoltaic platforms.